The Effectiveness of Computer-Based Games as A Learning Media on The IUPAC Name of Inorganic Compounds - Rusly Hidayah; Nuril Lailiyah Iswahyuni; Rista Ajeng Mitasari (Universitas Negeri Malang, 2021)
Learning media made must meet the eligibility criteria, one of which is effectiveness. The research was aimed to examine the effectiveness of computer-based games as a learning media on the nomenclature of an inorganic compound topic. This research used Plomp design research, which consists of three phases: preliminary phase, design prototype phase, and assessment phase. This research trial was 28 students in X grade at Senior High School 1 Puri Mojokerto used one group pretest and posttest design. The game's effectiveness s is based on the n-gain score from the pretest and posttest results, which data is normalized by Kolmogorov-Smirnov non-parametric test. The results of the n-gain calculation are 71.4% of students in one class have a moderate n-gain category, 21.42 % of students have a high n-gain category, and 7.18% of students have low n-gain criteria. Thus, it can be concluded that computer-based games are effective learning media. REFERENCES Arsyad, A. (2013). Media Pembelajaran. Jakarta: PT RajaGrafindo Persada. Brensell, & Hansen, C. (2010). Designing an Educational Game: Design Principles From a Holistic Perspective. International Journal of Learning, 17 (10), 279-920. Chandel, P. D. (2015). Digital Game-Based Learning in Computer Science Education. CPUH Res. J 1(2), 33-37. Dananjaya, U. (2017). Media Pembelajaran Aktif cetakan ke-4. Bandung: Nuansa Cendekia. Hake, R. R. (1998). Interactive Engagement Versus Traditional Methods: A Six Thousand Student Survey of Mechanics Test Data for Introductory Physics Courses. 66. Lutfi, A., & Hidayah, R. (2017). Activating Student to Learn Chemistry using Chemmy Card 6-1 Game as an Instructional Medium in IUPAC Nomenclature of Inorganic Compound Manero, B. e. (2015). Can Educational Video Games Increase High School Students' Interest In Theatre? Computers and Education Journal, 182-191. Maulidina, M. A., Susilaningsih, & Abidin, Z. (2018). Pengembangan Game Based Learning Berbasis Pendekatan Saintifik Pada Siswa Kelas IV Sekolah Dasar. Jurnal Teknologi Pendidikan, Fakultas Ilmu Pendidikan, Universitas Negeri Malang, 113- Nunes, Lima, Miranda, Junior, Alexandre, Carlos, et al. (2017). Nomenclature Bets: An Innovative Computer-Based Game To Aid Students in the Study of Nomenclature of Organic Compounds. Journal of Chemical Education (95), 899-902. Permendikbud. (2014). Peraturan Pemerintah No. 32 Tahun 2013 tentang Standar Kompetensi Lulusan dan Standar Isi. Jakarta: Permendikbud. Plomp, T. (2013). Educational Design Research: An Introduction. Enschede: SLO Netherland Institute for Curriculum Development. Riduwan. (2016). Skala Pengukuran Variabel-Variabel Penelitian. Bandung: Alfabeta. Sadiman. (2014). Media Pendidikan. Jakarta: PT Raja Grafindo Persada. Sardiman. (2001). Interaksi dan Motivasi Belajar Mengajar. Jakarta: PT Raja Grafindo Persada. Slameto. (2010). Belajar dan Faktor-Faktor Yang Mempengaruhinya. . Jakarta: Rineka cipta. Slavin, R. E. (2011). Psikologi Pendidikan : Teori dan Praktek Edisi Sembilan. Jakarta: PT Indeks. Sugiyono. (2017). Metode Penelitian Pendidikan Pendekatan Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta. Supendi, Pepen, & Nurhidayat. (2007). Fun Game. Jakarta: Penerba Swadaya.